2016
DOI: 10.3325/cmj.2016.57.151
|View full text |Cite
|
Sign up to set email alerts
|

Putative anticancer potential of novel 4-thiazolidinone derivatives: cytotoxicity toward rat C6 glioma in vitro and correlation of general toxicity with the balance of free radical oxidation in rats

Abstract: AimTo evaluate the cytotoxic action of 4-thiazolidinone derivatives (ID 3288, ID 3882, and ID 3833) toward rat glioma C6 cells and to compare the effects of these compounds and doxorubicin on the balance of free radical oxidation (FRO) and antioxidant activity (AOA) in the serum of rats.MethodsGlioma cells were treated with ID 3882, ID 3288, ID 3833, and doxorubicin, and their cytotoxicity was studied using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay and Trypan blue exclusion test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 22 publications
5
34
0
Order By: Relevance
“…In vitro evaluation of the vitality and survival (MTT assay and Trypan blue exclusion test) of treated cells revealed the following ranking of toxicity of 4-thiazolidinone derivatives towards C6 rat and U251 human glioma cells: 3882 < 3288 < 3833 ≈ doxorubicin [14,25]. In vivo study (rats) of the biochemical indicators of cardio- [26], hepato- [13] and nephrotoxic [27] actions of the applied drugs showed the same ranking.…”
Section: •-mentioning
confidence: 80%
See 3 more Smart Citations
“…In vitro evaluation of the vitality and survival (MTT assay and Trypan blue exclusion test) of treated cells revealed the following ranking of toxicity of 4-thiazolidinone derivatives towards C6 rat and U251 human glioma cells: 3882 < 3288 < 3833 ≈ doxorubicin [14,25]. In vivo study (rats) of the biochemical indicators of cardio- [26], hepato- [13] and nephrotoxic [27] actions of the applied drugs showed the same ranking.…”
Section: •-mentioning
confidence: 80%
“…The activation of FRO leads to a pathological process causing the frequent intoxication of the organism [13,14]. The results of studying the effect of experimental compounds (4-thiazolidinone derivatives -Les-3288, Les-3833 and Les-3882) on ROS and RNS concentration in blood serum of rats are shown on Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, we have demonstrated the pro-apoptotic action of the Les-3288 compound toward rat glioma cells of C6 line that possessed even higher toxicity for these cells than that of the Dox (25). In present study, we addressed the mechanisms of the pro-apoptotic action of the compound Les-3288, TMZ and Dox in order to reveal potential differences in these mechanisms and, thus, consider them at planning the combined chemotherapy schemes for glioma treatment.…”
Section: Discussionmentioning
confidence: 97%